Bemcentinib as monotherapy and in combination with low-dose cytarabine in acute myeloid leukemia patients unfit for intensive chemotherapy: a phase 1b/2a trial - Loges, Sonja; Heuser, Michael; Chromik, Jörg; Sutamtewagul, Grerk; Kapp-Schwoerer, Silke; Crugnola, Monica; Di Renzo, Nicola; Lemoli, Roberto; Mattei, Daniele; Fiedler, Walter; Alvarado-Valero, Yesid; Ben-Batalla, Isabel; et al. (Nature Communications, 2025)
Beyond first line, the prognosis of relapsed/refractory (R/R) acute myeloid leukemia (AML) patients is poor with limited treatment options. Bemcentinib is an orally bioavailable, potent, highly selective inhibitor of AXL, a receptor tyrosine kinase associated with poor prognosis, chemotherapy resistance and decreased antitumor immune response. We report bemcentinib monotherapy and bemcentinib+low-dose cytarabine combination therapy arms from the completed BerGenBio-funded open-label Phase 1/2b trial NCT02488408 (www.clinicaltrials.gov), in patients unsuitable for intensive chemotherapy. The primary objective in the monotherapy arm was identification of maximum tolerated dose with secondary objectives to identify dose-limiting toxicities, safety and efficacy, and bemcentinib pharmacokinetic profile. In the combination arm, the primary objective was safety and tolerability, with efficacy and pharmacokinetics as secondary objectives. Safety and tolerability were based on standard clinical laboratory safety tests and Common Terminology Criteria for Adverse Events version 4. Bemcentinib monotherapy (32 R/R, 2 treatment-naïve AML and 2 myelodysplasia patients) was well-tolerated and a loading/maintenance dose of 400/200 mg was selected for combination treatment, comprising 30 R/R and 6 treatment-naïve AML patients. The most common grade 3/4 treatment-related adverse events were cytopenia, febrile neutropenia and asymptomatic QTcF prolongation, with no grade 5 events reported. In conclusion, bemcentinib+low-dose cytarabine was safe and well tolerated.